EVALUATION OF PENTRAXIN 3 UTILITY IN PREDICTING MORTALITY IN GERIATRIC PATIENTS WITH COVID-19: A PROSPECTIVE STUDY - Senol, Arzu; Balin, Safak Ozer; Telo, Selda (Turkish Geriatrics Soc, 2022)
Introduction: The clinical spectrum of coronavirus disease (COVID-19) ranges from mild upper respiratory tract infections to fulminant pneumonia. Nevertheless, it is associated with high rates of morbidity and mortality in elderly individuals. The present study aimed to investigate the levels of pentraxin 3 in geriatric patients with COVID-19 and to determine whether it could serve as a marker for predicting mortality. Materials and Method: This study included patients aged >= 65 years who were diagnosed with COVID-19 infection and admitted to the pandemic ward between October 2021 and march 2022. The patients were classified into two groups: survivors and nonsurvivors.Results: Of the 95 geriatric patients included in this study, 20 (21%) died and 75 (79%) were discharged upon full recovery. There was a significant difference between male and female patients in terms of mortality. Shortness of breath was noted in 19 nonsurvivors and 9 survivors (p < 0.05). The median pentraxin 3 level was 5.8 ng/mL (1-20) for all patients, 3.92 ng/mL (1-19.6) for survivors, and 6.3 ng/mL (4.1-20) for nonsurvivors (p < 0.001). The area under the curve in the receiver operating characteristic curve analysis for pentraxin 3 was 0.596 (p = 0.04) to predict mortality. The likelihood ratio test revealed a cutoff value of 4.43 ng/mL (sensitivity: 57.1% and specificity: 70.5%) for pentraxin 3.Conclusion: Pentraxin 3 was found to be a novel biomarker for predicting mortality in geriatric patients with COVID-19, and it was investigated for the first time in this special population.
Keywords: COVID-19; Geriatrics; Mortality; Acute-Phase Proteins